The impact of environmental health facilities and maternal behaviors on the incidence of diarrhea among children under five - Yusmidiarti Yusmidiarti; Adi Heru Husodo; Susi Iravati; Risda Yulianti (Healthcare in Low-resource Settings)
The objectives of this study were to determine the prevalence of diarrhea among children under five and assess the relationship between its risk factors related to environmental health facilities and maternal behavior. A prospective case-control community-based study was conducted in the service area of Pasar Ikan Community Health Center, Teluk Segara Subdistrict, Bengkulu City, Indonesia. A total of 140 participants were included, comprising 70 cases and 70 controls. The study found that poor qualification of clean water resources (OR=4.026, p-value=0.000), inadequate utilization of clean water (OR=5.813, p-value=0.000), poor qualification of family latrines (OR=3.574, p-value=0.000), and inadequate utilization of family latrines (OR=3.377, p-value=0.001) were significantly associated with an increased risk of diarrhea prevalence among children under five. Furthermore, unhealthy mothers’ behaviors, including frequent feeding of children outside the home (OR=2.728, p-value=0.000) and poor personal hygiene (OR=3.377, p-value=0.001), were also significantly related to a higher prevalence of diarrhea in this age group. Therefore, both substandard environmental health facilities and unhealthy maternal behaviors were identified as significant risk factors for diarrhea prevalence in children under five. These findings emphasize the critical importance of improving environmental health facilities and promoting positive changes in mothers’ behavior to reduce the incidence of diarrhea in this vulnerable population.